THE NOVEL "SABO AND SAMANDAR" BY ULUGBEK HAMDAM (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
This article provides information about the role of the famous writer and critic Ulugbek Hamdam in the current literary process, his artistic works and scientific and critical activities. You can analyze his novel "Sabo and Samandar" and see how beautifully written the work is.